Update on management of post-prostatectomy incontinence in 2013 - Herschorn, Sender (Canadian Urological Association Journal, 2013)
Surgical intervention is often required to address urinary incontinence post-prostatectomy. This summary provides an overview of surgical intervention in post-prostatectomy incontinent patients and of the evidence supporting the various surgical interventions currently in use.